Managerial Accounting concepts for planning, control, decision making - Garrison, Ray H., D.B.A., CPA. (USA : IRWIN, 1991)
Contents of this book include: The foundation; The central theme; The capstone; Selected topics for further study.
Keywords: Accounting; Managerial accounting